Earth structures – a summary of the last 50 years - Ivan Vaníček (Acta Polytechnica CTU Proceedings)
This paper discusses changes and developments in the field of Earth Structures that have been presented and discussed over the last fifty years at the annual national conferences on Foundation Engineering held (with foreign participation) in the city of Brno.